Gender Involvement in Contemporary Economic Activities of Manide Tribe in Jose Panganiban, Camarines Norte, Philippines: Basis for Capacity Development Program - Maria Cristina C. Azuelo; Ma. Reina A. Mabeza (Journal of Social Entrepreneurship Theory and Practice, 2021)
This descriptive quantitative research study was conducted to determine the gender involvement in the Manide Tribe's contemporary economic activities and formulate a capacity development program for Mamanide people to acquire knowledge and uplift their economic condition. Findings reveal that the 53 Mamanide respondents, obtained by complete enumeration, are involved in contemporary economic activities like the external labor market for males and the sale of agricultural products for females. The majority of females are involved in saving and storing compared to males. Both respondents are interested in buying basic needs and producing crops and farm products. Their very high level of gender involvement has been accounted for in the external labor market, spending, and production; however, in saving and storing, the male has no involvement while the female has a high level of involvement. As to the contributing factors, the social, economic, environmental, and political factors have a very high contribution to the changes in their economic systems. The study identified areas that need to be addressed through the formulation and implementation of the Capacity Development Program.